Real Estate Investments in Germany
XVIII, 346 p.
Keywords: The real estate market in Germany has recovered remarkably well from 2008/09 crisis. Portfolio transactions, infrastructure projects as well as investments in commercial and residential real estate are on the rise. This publication provides investors, property developers and advisers with a practical guideline to the legal, tax and commercial framework for real estate investments in Germany.